Traditional Musical Instruments and Dance Music of the Lundayeh of Sabah - Jinky Jane C. Simeon,; Low Kok On,; Ian Stephen Baxter,; Maine Saudik,; Saniah Ahmad,; Chong Lee Suan, (Wacana Seni Journal of Arts Discourse, 2017)
The Lundayeh community, the focus of this study, is an ethnic group found mainly in the districts of Tenom and Sipitang, in the Malaysian state of Sabah. Recent field trips to Lundayeh villages in these two districts have confirmed the group as rich in various forms of traditional dance music namely busak bunga, busak paku, alai sekafi and gong beats that serve a diverse range of purposes and functions in their daily life. Different types of traditional dance music are produced by a variety of traditional musical instruments. This preliminary study intends to explore and analyse the intricacies of Lundayeh traditional musical instruments found in Tenom and Sipitang, the aspects of the community's musical instruments and their functions, and the music transcriptions produced from selected instruments. It is hoped that this study could help shed light into the Lundayeh traditional dance music and their musical instruments.